4 - La politique industrielle: controverses et démarche stratégique en Afrique au Sud du Sahara: le cas du Sénégal: by Seck Alioune - Seck Alioune (Africa Development, 1993)
Underdevelopment is first and foremost a problem of under - industrialization. Hence states intervene to build industrial systems through the setting up of industrial policies. These policies underline the public prerogatives of the states as well as their political ideologies, hence the debate on the role of the state in intentional andlor unintentional mode of regulation of the market, the forms and limits of public intervention, the role of the market and competition and economic and social regulation. The theory of industrial policy raises the issue of its formalization, hence the various analytical and normative approaches. Industrial policy is first and foremost a strategy designed to reach some targets. In Africa, it has more and more taken a supranational dimension. However it still remains vulnerable to economic and financial crises.